Ultrasound-Guided Femoral Nerve Blocks. Issue 12 (December 2015) - Baker, Mark D.; Gullett, John P.
Abstract : Abstract: Pediatric acute femur fractures are a relatively common major orthopedic injury seen in emergency departments. Providing adequate and safe analgesia is essential while patients await definitive management of these fractures. Opioid medications are typically used to treat fracture-associated pain but have well-known adverse effects including respiratory and central nervous system depression, pruritus, nausea, and allergic reactions. Dose titration of opioids in pediatric patients may be difficult and requires frequent nursing and physician reassessments. Regional anesthesia using ultrasound guidance has been proposed as a reliable and safe method to provide pain relief for this population and to decrease reliance on opioid medications. There is a growing body of literature on the utility and safety of ultrasound-guided femoral nerve blocks for pediatric patients in the acute care setting. This review article covers recent literature on point-of-care ultrasound-guided femoral nerve blocks for pediatric patients, with a discussion of the indications, sonographic anatomy, selection of anesthetics, nerve block technique, and complications. This review supplements the expert supervision and practice required to gain competency.